Assistance in the Planning of Retaining Walls on Semut Island Tourism Objects: Pendampingan Pembuatan Perencanaan Dinding Penahan Tanah Pada Objek Wisata Pulau Semut - Muthia Anggraini; Haris, Virgo Trisep; Saleh, Alfian (Yayasan Ahmar Cendekia Indonesia, 2023)
Pengambangan is an area located in the Limbungan Village which has tourism potential on the banks of the Siak River so that it can be developed into a natural tourist attraction. Its location on the Siak River makes it a tourist attraction that resembles an island located between the Siak River and the mouth of the river. The ebb and flow of river water plus water waves caused by boats and speedboats crossing the area so that the waves can erode the cliffs of the Semut Island tourist attraction. The purpose of this service is to assist partners in building retaining walls. The method used is lectures and discussions. The result is that the design of the retaining wall is made of the type of wire gabion that is adapted to the conditions of the location. The work items are gabion work, geotextile (non-woven) work, surface embankment work, and cliff-fill embankment workThis counseling helps partners in assisting with planning and retaining walls. Abstrak Pengambangan merupakan daerah yang berada di Kelurahan Limbungan yang memiliki potensi wisata yang berada di tepi Sungai Siak sehingga dapat dikembangkan menjadi objek wisata alam. Lokasinya yang berada di sungai siak mengakibatkan objek wisata yang menyerupai pulau yang berada diantara sungai siak dan muara sungai. Pasang surut air sungai ditambah gelombang air yang diakibatkan oleh perahu dan speedboat yang melintasi wilayah tersebut sehingga gelombang dapat mengikis tebing dari objek wisata Pulau Semut. Tujuan pengabdian yaitu mendampingi mitra dalam membuat dinding penahan tanah. Metode yang dilakukan dengan ceramah dan diskusi. Hasilnya perencanaan dinding penahan tanah dibuat adalah tipe bronjong kawat yang disesuaikan dengan kondisi lokasinya. Item pekerjaan yaitu pekerjaan bronjong, pekerjaan geotextile (non woven), pekerjaan timbunan permukaan, dan pekerjaan timbunan pengisi tebing. Penyuluhan ini membantu mitra dalam pemdampingan membuat perencanaan dan dinding penahan tanah.